Addressing the right to food through agriculture cooperatives : a case study of Zimbabwe and Tanzania - Persaud, Sarojini (University of Pretoria, 2025)
Mini Dissertation (LLM (Multidisciplinary Human Rights))--University of Pretoria, 2025.